Comparison of TCB And Picterus Joundice Bilirubin Examination In Newborns at RSA UGM in 2025 - Dewi Krismayanti; Nurul Aidayasari (Rumah Sakit Akademik Universitas Gadjah Mada, 2026)
Background: One of the health problems often experienced by infants is jaundice neonatorum, which is a condition where bilirubin levels are above 10 mg%. Based on a study performed in the infant room at RSA UGM in December 2024, the incidence of newborns who are treated with phototherapy is more than 50%. Transepidermal Bilirubinometry is a non-invasive bilirubin screening tool for infants with a gestational age of more than 36 weeks and born after 24 hours, born by working with optical spectroscopy, with bilirubin in the skin. The jaundice screening device is certified for clinical use. A photo was taken and analyzed to display bilirubin levels within a few seconds (Product licence by Ministry of Health Number 20101323603).Objective: This study aims to determine whether there are differences in the results of bilirubin examination using Transcutaneous Bilirubinometry and Petechiae Jaundice.Method: This research involved newborns who were full-term or more than 37 weeks of gestation, had a birth weight of more than 2500 grams, and were at least 24 hours old.Result: This study was conducted at RSA UGM from April to July 2025. The sampling technique used was accidental sampling. Out of 42 participants, 23.8% had a gestational age of less than 38 weeks, 69% had a gestational age between 38 and 40 weeks, and 7.2 % had a gestational age of more than 40 weeks. From the data analysis of 42 newborns, the bilirubin levels using Transcutaneous Bilirubin had an average of 8.14 mg/dl. while the bilirubin levels using Picterus had an average of 7.90 mg/dl. Analysis using a paired sample T-test to compare the averages of two data groups showed a statistically significant difference. The results showed a significance value of 0.000 for the TCB Bilirubin and Picterus Jaundice test. The significance level for Picterus bilirubin is 0.000. A P value < 0.05 indicates that the results do not show a significant difference in measuring bilirubin using Picterus Jaundice and Transcutaneous Bilirubin.Conclusion: Picterus Jaundice can be used as an alternative method in screening or examining bilirubin in newborns.